Petrology, Geochemical Characteristics, Tectonic Setting, and Implications for Chromite and PGE Mineralization of the Hongshishan Alaskan-Type Complex in the Beishan Orogenic Collage, North West China - Wang, Zhaolin; Zheng, Xiaoming; Meng, Guixiang; Tang, Hejun; Fang, Tonghui (Frontiers in Earth Science, 2021)
The Hongshishan mafic-ultramafic complex is situated in the north of the Beishan orogenic collage and the southern part of the Central Asian Orogenic Belt. This paper outlines the petrological, geochemical, and mineralogical data of the Hongshishan ultramafic–mafic complex in the Beishan orogenic collage to constrain its tectonic setting and mineralization. The lithological units of the complex include dunite, clinopyroxene peridotite, pyroxenite, and gabbro. The complex showed concentric zonation, from clinopyroxene peridotite and dunite in the core to pyroxenite and gabbro in the margin. These ultramafic–mafic rocks are characterized by cumulate and layering textures. Field observations, petrography, and significant elemental composition variation, a decreasing sequence of ferromagnesian minerals (Mg#), olivine Fo, and spinel Cr#, all show fractional crystallization trends from dunites through clinopyroxene peridotite and pyroxenite, to gabbros. There are systematic trends among the primary oxides, e.g., CaO, TiO2, and Al2O3, with MgO, suggesting a fractional crystallization trend. SiO2 and Al2O3 increased, which coupled with decreasing MgO, suggested olivine fractionation. The negative correlations of CaO and Al2O3 with MgO meant the accumulation of spinel and mafic minerals. The compositions of olivines from the dunite and clinopyroxene peridotite in the Hongshishan plot within the Alaskan Global trend fields displayed a typical fractional crystallization trend similar to olivines in an Alaskan-type complex. The clinopyroxenes in the clinopyroxene peridotite primarily occur as a diopside and appear in the field of an Alaskan-type complex. The absence of orthopyroxene, less hydrous, and free of fluid inclusions in the chrome spinels means the absence of a magmatic origin of chromite-bearing peridotites in hydrous parental melts or scarce hydrous melts. Serpentinization, carbonatization, subduction modification, and enrichment may account for the LILE-enrichment and HFSE-depletion of peridotite rocks. Negative Eu anomalies and REE fractionations of mafic-ultramafic rocks may not be directly attributed to crustal assimilation. Petrological, mineralogical, and geochemical characteristics indicated the Hongshishan complex is not the member compositions of a typical ophiolite. However, it displays many similarities to Alaskan-type mafic-ultramafic intrusions related to subduction or arc magmas setting at ∼366.1 Ma and suffered subduction modification and enrichment. The Hongshishan complex is a unique Ir-Ru-rich chromite deposit in the southern margin of the Altaids orogenic belt. Chromites occur primarily in light yellow dunites, with banded, lenticular, veined, thin-bedded, and brecciated textures. Part of the chromite enrichment in IPGE (Os, Ir, Ru) and the chondrite-normalized spider diagram of PGE showed steep right-facing sloped patterns similar to those of the PGE-rich ophiolitic chromites.